An Ni-based coordination polymer with a bamboo-like crystal structure - Yi Li; Wang Xie; Chen Lin (Acta Crystallographica Section E: Crystallographic Communications)
An Ni-based coordination polymer, namely, poly[tetraaquabis[4,7-bis(1H-pyrazol-4-yl)benzo[c][1,2,5]thiadiazole][μ4-5,5′-(1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)diisophthalato]dinickel(II)], {[Ni2(C30H10N2O12)(C12H8N6S)2(H2O)4]·2C3H7NO·H2O}n or Ni-BIBT-BINDI, with a crystal structure reminiscent of bamboo has been synthesized, the Ni2+ ions exhibiting a slightly distorted octahedral coordination geometry with N atoms and O atoms. The bond lengths of the Ni—O bonds range from 2.032 to 2.121 Å, and those of the Ni—N bonds are approximately 2.080 Å. The BINDI ligands are connected to each other by the Ni—O bonds, which form the backbone of the bamboo, while the BIBT ligands are connected to the backbone of the bamboo through Ni—N bonds and grows on both sides of the bamboo, constituting the bamboo leaves.